β-2 Adrenergic Receptor Gene Variations, Blood Pressure, and Heart Size in Normal Twins - Busjahn, Andreas; Li, Guo-Hua; Faulhaber, Hans-Dieter; Rosenthal, Magda; Becker, Albert; Jeschke, Eva; Schuster, Herbert; Timmermann, Bernd; Hoehe, Margret R.; Luft, Friedrich C. (Hypertension (Dallas, Tex. 1979), 2000)
ABSTRACTGenetic variability, which influences cardiovascular phenotypes in normal persons, is likely to be relevant to cardiovascular disease. We studied normal monozygotic and dizygotic twins and found strong genetic influences on blood pressure and heart size. We then relied on the dizygotic twins and their parents to apply molecular genetic techniques. We performed a linkage analysis with markers close to the β-2 adrenergic receptor (AR) gene locus in the dizygotic twins and their parents and found strong evidence for linkage to the quantitative traits of blood pressure and heart size. We then used allele-specific polymerase chain reaction to genotype the subjects further. We performed an association analysis and found that 4 functionally relevant polymorphisms in the β-2 AR gene, namely Arg16/Gly, Gln27/Glu, Thr164/Ile, and a variant in the promoter region (−47C/T), were variably associated with blood pressure and heart size differences but were in linkage dysequilibrium with each other. A subsequent conditional analysis suggested that the Arg16/Gly polymorphism exerted the predominant effect. These findings underscore the importance of the β-2 AR gene to blood pressure regulation, heart size, and probably to the development of hypertension. We suggest that a combined linkage and association approach will elucidate the genetic variability influencing blood pressure and other cardiovascular phenotypes.